Transitivity in Eastern Mansi : An Information Structural Approach - Virtanen, Susanna (Helsingin yliopisto, 2015)
The dissertation consists of four articles published in peer-reviewed linguistic journals and an introduction. The aim of the study is to provide a description of the formal means of expressing semantic transitivity in the Eastern dialects of the Mansi language (EM), as well as of the variation between the different means. The study is connected to Uralic studies and functional-linguistic typology. Mansi is a Uralic language spoken in Western Siberia. Unfortunately, its Eastern dialects died out some decades ago, but there are still approximately 2700 speakers of Northern Mansi. Because it is no longer possible to access any live data on EM, the study is based on written folkloric materials gathered by Artturi Kannisto about 100 years ago. From the typological point of view, Mansi is an agglutinative language with many inflectional and derivational suffixes. The study is based on information structural analysis, particularly the terminology and definitions proposed by Lambrecht (1994). The approach is based on three main pragmatic functions, primary topic, secondary topic and focus, and on how they correlate with syntactic functions and how their morphological markedness or unmarkedness is due to information structural factors. Further, the notion of topicality is connected to the concept of Differential Object Marking (DOM) and the observations of Iemmolo (2010/2011). According to the data of this study, DOM is based on topicality in EM. Finally, the analysis is expanded to include variation between the active voice and the passive voice and variation in three-participant constructions. The topic of the study can be divided into three different sub-topics: 1) marking of the DO, 2) variation in three-participant constructions and 3) variation between the active voice and the passive voice. The main result of the study is a complex description of how the whole system of expressing semantic transitivity in EM is based on the same principles. Among others, the results of the study also show some new aspects that ...